Thermal insulation material for hard rock tunnel in cold region as well as preparation method and application of thermal insulation material

By using an insulation material containing pretreated silica and hydrophobic vitrified microbeads in the cold hard rock tunnel, the problems of high thermal conductivity and severe freeze-thaw damage in the cold hard rock tunnel are solved, and efficient insulation and durability are achieved.

CN119591379AActive Publication Date: 2025-03-11INST OF ROCK & SOIL MECHANICS CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411633399.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-11
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the thermal conductivity and freeze-thaw damage of concrete in hard rock tunnels in cold zones, while maintaining strength and durability.

Method used

A thermal insulation material is used, and its raw materials include cement, pretreated silica, fly ash, thermal insulation aggregate, machined sand, potassium silicate, water reducing agent, defoaming agent and quick-setting agent. The pretreated silica is prepared by a combination of nylon 66, formic acid solution and nanographene oxide to form an aerogel structure; hollow vitrified microbeads are combined with acid-base treatment and fluorosilane coupling agent to form hydrophobic vitrified microbeads.

Benefits of technology

It significantly reduces the thermal conductivity of concrete, improves thermal insulation performance, reduces the risk of freeze-thaw damage and cracking, and ensures later strength development and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591379A_ABST
    Figure CN119591379A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cold region hard rock tunnel concrete, and particularly discloses a thermal insulation material for a cold region hard rock tunnel as well as a preparation method and application of the thermal insulation material. The thermal insulation material for the hard rock tunnel in the cold region is prepared from the following raw materials in parts by mass: 70 to 100 parts of cement, 10 to 14 parts of pretreated silicon dioxide, 10 to 16 parts of fly ash, 10 to 20 parts of thermal insulation aggregate, 100 to 120 parts of machine-made sand, 0.5 to 1.2 parts of potassium silicate, 2 to 2.6 parts of water reducing agent, 0.1 to 0.5 part of defoaming agent, 1 to 2 parts of accelerator and 17 to 22 parts of water, the pretreated silicon dioxide is prepared by the following specific operation: adding nylon 66 into a formic acid solution, stirring at 60-80 DEG C for 1-2 hours, adding tetraethoxysilane, continuously stirring for 10-20 minutes, adding nano graphene oxide, stirring for 1-2 hours, cooling to-100 to-80 DEG C, keeping the temperature for 1-2 hours, and freeze-drying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cold region hard rock tunnel concrete, and in particular to a thermal insulation material for cold region hard rock tunnels, and a preparation method and application thereof. Background Art

[0002] Tunnels have the advantages of overcoming terrain obstacles, shortening spatial distances, and improving the operation quality of land transportation projects. In recent years, tunnels have gradually developed in the direction of "deep burial and long growth", and various problems accompanying them have become increasingly prominent.

[0003] my country is building more and more tunnels in cold regions. Due to the large temperature changes in cold regions, the tunnel lining structure is subjected to temperature stress caused by large temperature changes. At present, the thermal conductivity of shotcrete is mainly reduced by extending the heat transfer path inside the concrete and introducing air holes with low thermal conductivity. For example, fiber-insulated concrete is made by introducing low thermal conductivity fibers. It reduces thermal conductivity by increasing the heat transfer path through fiber orientation, but the thermal insulation performance is weak. If lightweight aggregate concrete is made by introducing multi-void lightweight aggregate, although the thermal conductivity can be greatly reduced, the strength of the concrete is poor due to its rich pore structure.

[0004] At present, the early hydration rate of shotcrete insulation materials is too fast, which affects the later strength development. In addition, the frost heave force in cold environments can easily cause freeze-thaw damage to the concrete, forming shrinkage cracks, which will not only result in poor insulation effect, but also cause a significant loss of strength and affect durability. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a thermal insulation material for hard rock tunnels in cold regions and a preparation method and application thereof.

[0006] A thermal insulation material for hard rock tunnels in cold regions, wherein the raw materials include, by mass, 70-100 parts of cement, 10-14 parts of pretreated silica, 10-16 parts of fly ash, 10-20 parts of thermal insulation aggregate, 100-120 parts of machine-made sand, 0.5-1.2 parts of potassium silicate, 2-2.6 parts of water reducer, 0.1-0.5 parts of defoamer, 1-2 parts of accelerator, and 17-22 parts of water; the pretreated silica is The specific preparation operation is as follows: add nylon 66 to formic acid solution, stir at 60-80°C for 1-2h, add ethyl orthosilicate and continue stirring for 10-20min, add nano-graphene oxide and stir for 1-2h, cool to -100 ~ -80°C, keep warm for 1-2h, and freeze-dry; the thermal insulation aggregate includes: hydrophobic vitrified microspheres and expanded perlite, and the mass ratio of hydrophobic vitrified microspheres to expanded perlite is 10:1-3.

[0007] Preferably, the mass ratio of nylon 66, tetraethyl orthosilicate and nano-graphene oxide is 1-5:5-10:1-2.

[0008] Preferably, the mass fraction of the formic acid solution is 70-80%.

[0009] Preferably, the hydrophobic glass microspheres are prepared by the following specific operation: adding the hollow glass microspheres to a sulfuric acid solution, stirring at 40-50°C for 10-20 min, filtering, washing, drying, adding to an ammonia solution, stirring at 40-50°C for 10-30 min, filtering, washing, drying, adding to an ethanol aqueous solution, adding a fluorinated silane coupling agent thereto, adjusting the pH value of the system to 3-4, stirring at 70-80°C for 1-2 h, filtering, and drying.

[0010] Preferably, the mass ratio of the hollow glass microspheres to the fluorine-containing silane coupling agent is 10-30:1-2.

[0011] Preferably, the fluorine-containing silane coupling agent is tridecafluorooctyl triethoxysilane or perfluorooctanesulfonylaminopropyl triethoxysilane.

[0012] Preferably, the quick-setting agent is prepared by the following specific operation: aluminum sulfate, citric acid, aluminum hydroxide, early strength agent, dispersant and water are mixed, stirred at 70-90° C. for 1-2 hours, organic alcohol amine is added, stirred for 1-2 hours, and cooled to room temperature.

[0013] Preferably, the mass ratio of aluminum sulfate, citric acid, aluminum hydroxide, early strength agent, dispersant, water and organic alcohol amine is 1-3:0.1-0.5:1-2:1-2:1-2:10-20:1-2.

[0014] Preferably, the organic alcohol amine is at least one of ethanolamine, diethanolamine and triisopropanolamine.

[0015] Preferably, the early strength agent is calcium formate and / or sodium nitrate.

[0016] Preferably, the dispersant is sodium methylene bisnaphthalene sulfonate.

[0017] The above-mentioned method for preparing the thermal insulation material for hard rock tunnels in cold regions comprises the following steps:

[0018] S1. Stir cement, pretreated silica, fly ash and thermal insulation aggregate for 50-100 seconds to obtain a premix;

[0019] S2. Add machine-made sand, potassium silicate and water to the premix and mix evenly. Then add water reducer, defoamer and accelerator and stir for 5-15s.

[0020] The above-mentioned method for applying the thermal insulation material for hard rock tunnels in cold regions comprises the following steps: pre-wetting the surface to be sprayed, and then spraying the above-mentioned thermal insulation material for hard rock tunnels in cold regions onto the surface, with a spraying thickness of 30-50 mm.

[0021] Beneficial effects:

[0022] The present invention dissolves nylon 66 in a formic acid solution, deposits and combines nano-silicon dioxide particles on a PA66 skeleton, and then combines the nano-graphene oxide sheet structure to form an aerogel structure through freeze-drying. The aerogel structure not only has a large number of pore structures inside, but also can effectively extend the heat transfer route and greatly reduce the thermal conductivity coefficient. At the same time, it is compounded with cement and has good dispersibility in the slurry, which effectively increases the viscous resistance of floating in the slurry and significantly improves the homogeneity of the mixture.

[0023] The present invention combines the hollow vitrified microspheres with a fluorine-containing silane coupling agent after acid and alkali treatment, which not only has an excellent hydrophobic effect, but also is compounded with pretreated silica and cement to effectively reduce the density and thermal conductivity, improve thermal insulation performance, and make the mortar light and high-strength, which can improve the workability of the concrete mixture, reduce the rebound amount, and increase the thickness of a single injection.

[0024] The pretreated silica obtained by the present invention has a strong water retention and slow-release ability, and plays a role of water slow-release internal curing in the concrete of the cold eastern zone, which not only significantly reduces freeze-thaw damage, reduces the risk of cracking, ensures the later strength development, and improves durability, but also can compensate for shrinkage, reduce cracking, and extend the service life of the tunnel.

[0025] The invention has good construction performance, can be well adapted to hard rock tunnels in cold regions, effectively improves durability and crack resistance, and has a simple preparation method, and is suitable for large-scale promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a comparison chart of the initial setting time and final setting time of the thermal insulation material for hard rock tunnels in cold regions obtained in Example 5 and Comparative Examples 1-2.

[0027] Figure 2 This is a comparison chart of the 1d compressive strength and 28d compressive strength of the insulation materials for hard rock tunnels in cold regions obtained in Example 5 and Comparative Examples 1-2 after standard curing for 28d.

[0028] Figure 3 This is a comparison chart of thermal conductivity and early-age autogenous shrinkage of the insulation materials for hard rock tunnels in cold regions obtained in Example 5 and Comparative Examples 1-2 after standard curing.

[0029] Figure 4This is a comparison chart of the strength loss rates of the thermal insulation materials for hard rock tunnels in cold regions obtained in Example 5 and Comparative Examples 1-2 after standard curing for 28 days and then freezing and thawing 100 times. DETAILED DESCRIPTION

[0030] The present invention will be further explained below in conjunction with specific embodiments.

[0031] The parameters of the machine-made sand used are as follows: apparent density 2640kg / m 3 , bulk density (compact) 1710kg / m 3 , bulk density (loose) 1640kg / m 3 , mud content is 1.60%, water content is 0.36%, grading zone is super 1 zone, and fineness modulus is 3.37.

[0032] The polycarboxylate water reducer used below was purchased from Jiangsu Lai Te New Materials Co., Ltd., model number M171. The polyether modified silicone defoamer used below was purchased from Qingdao Meiside Silicone Co., Ltd., model number MSD-916.

[0033] The bulk density of the vitrified microspheres used below is 125 kg / m 3 , particle size is 0.25mm, cylinder pressure strength is 0.2MPa, thermal conductivity is 0.07W / (m·K). The particle size of the expanded perlite used below is 2-3mm.

[0034] Example 1

[0035] A thermal insulation material for hard rock tunnels in cold regions, the raw materials of which include: 70kg of PO 42.5 grade ordinary Portland cement, 10kg of pretreated silica, 10kg of grade II fly ash, 10kg of thermal insulation aggregate, 100kg of machine-made sand, 0.5kg of potassium silicate, 2kg of polycarboxylic acid water reducer, 0.1kg of polyether modified organic silicon defoamer, 1kg of accelerator, and 17kg of water.

[0036] The pretreated silica was prepared by the following specific operation: 1 kg of nylon 66 was added to 30 kg of 70% formic acid solution by mass, stirred at 60°C for 1 hour, 5 kg of ethyl orthosilicate was added and stirring continued for 10 minutes, 1 kg of nano-graphene oxide was added and stirred for 1 hour, the temperature was lowered to -100°C, kept warm for 1 hour, and freeze-dried.

[0037] The thermal insulation aggregate is composed of hydrophobic vitrified microspheres and expanded perlite in a mass ratio of 10:1. The hydrophobic vitrified microspheres are prepared by the following specific operations: 10 kg of hollow vitrified microspheres are added to 50 kg of 70% sulfuric acid solution, stirred at 40°C for 10 min, filtered, washed, dried, added to 50 kg of 10% ammonia solution, stirred at 40°C for 10 min, filtered, washed, dried, added to 50 kg of 30% ethanol aqueous solution, 1 kg of perfluorooctanesulfonylaminopropyl triethoxysilane is added thereto, hydrochloric acid is used to adjust the pH value of the system to 3-4, stirred at 70°C for 1 hour, the stirring speed is 1000 r / min, filtered, and dried.

[0038] The quick-setting agent is prepared by the following specific operation: 1 kg of aluminum sulfate, 0.1 kg of citric acid, 1 kg of aluminum hydroxide, 1 kg of calcium formate, 1 kg of sodium methylenebisnaphthalene sulfonate, and 10 kg of water are mixed, stirred at a temperature of 70°C for 1 hour, 1 kg of ethanolamine is added, stirred for 1 hour, and then cooled to room temperature.

[0039] The above method for preparing the thermal insulation material suitable for hard rock tunnels in cold regions comprises the following steps:

[0040] S1. Add PO 42.5 grade ordinary Portland cement, pretreated silica, grade II fly ash, and thermal insulation aggregate into a mixer, and stir at a speed of 100 r / min for 50 s to obtain a premix;

[0041] S2. Add machine-made sand, potassium silicate and water to the premix and mix evenly. Then add polycarboxylic acid water reducer, polyether modified silicone defoamer and accelerator and stir for 5 seconds.

[0042] Example 2

[0043] A thermal insulation material for hard rock tunnels in cold regions, the raw materials of which include: 100 kg of PO 42.5 grade ordinary Portland cement, 14 kg of pretreated silica, 16 kg of grade II fly ash, 20 kg of thermal insulation aggregate, 120 kg of machine-made sand, 1.2 kg of potassium silicate, 2.6 kg of polycarboxylic acid water reducer, 0.5 kg of polyether modified organic silicon defoamer, 2 kg of accelerator, and 22 kg of water.

[0044] The pretreated silica was prepared by the following specific operation: 5 kg of nylon 66 was added to 50 kg of 80% formic acid solution by mass, stirred at 80°C for 2 h, 10 kg of ethyl orthosilicate was added and stirring continued for 20 min, 2 kg of nano-graphene oxide was added and stirred for 2 h, cooled to -80°C, kept warm for 2 h, and freeze-dried.

[0045] The thermal insulation aggregate is composed of hydrophobic vitrified microspheres and expanded perlite in a mass ratio of 10:3. The hydrophobic vitrified microspheres are prepared by the following specific operations: 30 kg of hollow vitrified microspheres are added to 100 kg of 80% sulfuric acid solution, stirred at 50°C for 20 minutes, filtered, washed, dried, added to 100 kg of 20% ammonia solution, stirred at 50°C for 30 minutes, filtered, washed, dried, added to 100 kg of 50% ethanol aqueous solution, 2 kg of tridecafluorooctyl triethoxysilane are added thereto, hydrochloric acid is used to adjust the pH value of the system to 3-4, stirred at 80°C for 2 hours at a stirring speed of 4000 r / min, filtered, and dried.

[0046] The quick-setting agent is prepared by the following specific operation: 3 kg of aluminum sulfate, 0.5 kg of citric acid, 2 kg of aluminum hydroxide, 2 kg of sodium nitrate, 2 kg of sodium methylenebisnaphthalene sulfonate, and 20 kg of water are mixed, stirred at a temperature of 90° C. for 1-2 hours, 2 kg of diethanolamine is added, stirred for 2 hours, and then cooled to room temperature.

[0047] The above method for preparing the thermal insulation material suitable for hard rock tunnels in cold regions comprises the following steps:

[0048] S1. Add PO 42.5 grade ordinary Portland cement, pretreated silica, grade II fly ash, and thermal insulation aggregate into a mixer, and stir at a speed of 200 r / min for 100 s to obtain a premix;

[0049] S2. Add machine-made sand, potassium silicate and water to the premix and mix evenly. Then add polycarboxylic acid water reducer, polyether modified silicone defoamer and accelerator and stir for 15 seconds.

[0050] Example 3

[0051] A thermal insulation material for hard rock tunnels in cold regions, the raw materials of which include: 80kg of PO 42.5 grade ordinary Portland cement, 13kg of pretreated silica, 12kg of grade II fly ash, 18kg of thermal insulation aggregate, 105kg of machine-made sand, 1kg of potassium silicate, 2.2kg of polycarboxylic acid water reducer, 0.4kg of polyether modified organic silicon defoamer, 1.3kg of accelerator, and 21kg of water.

[0052] The pretreated silica was prepared by the following specific operation: 2 kg of nylon 66 was added to 45 kg of 73% formic acid solution by mass, stirred at 75°C for 80 min, 9 kg of ethyl orthosilicate was added and stirred for 12 min, 1.7 kg of nano-graphene oxide was added and stirred for 80 min, the temperature was lowered to -85°C, kept warm for 80 min, and freeze-dried.

[0053] The thermal insulation aggregate is composed of hydrophobic vitrified microspheres and expanded perlite in a mass ratio of 10:2.5. The hydrophobic vitrified microspheres are prepared by the following specific operations: 15 kg of hollow vitrified microspheres are added to 90 kg of 73% sulfuric acid solution, stirred at 48 ° C for 12 minutes, filtered, washed, dried, added to 90 kg of 12% ammonia solution, stirred at 48 ° C for 15 minutes, filtered, washed, dried, added to 90 kg of 35% ethanol aqueous solution, 1.7 kg of perfluorooctanesulfonylaminopropyl triethoxysilane is added thereto, hydrochloric acid is used to adjust the pH value of the system to 3-4, stirred at 73 ° C for 100 minutes, the stirring speed is 2000r / min, filtered, and dried.

[0054] The accelerator is prepared by the following specific operation: 2.5 kg of aluminum sulfate, 0.2 kg of citric acid, 1.7 kg of aluminum hydroxide, 1.2 kg of sodium nitrate, 1.7 kg of sodium methylenebisnaphthalene sulfonate, and 12 kg of water are mixed, stirred at a temperature of 85° C. for 80 min, 1.7 kg of triisopropanolamine is added, stirred for 80 min, and cooled to room temperature.

[0055] The above method for preparing the thermal insulation material suitable for hard rock tunnels in cold regions comprises the following steps:

[0056] S1. Add PO 42.5 grade ordinary Portland cement, pretreated silica, grade II fly ash, and thermal insulation aggregate into a mixer, and stir at a speed of 180 r / min for 90 s to obtain a premix;

[0057] S2. Add machine-made sand, potassium silicate and water to the premix and mix evenly. Then add polycarboxylic acid water reducer, polyether modified silicone defoamer and accelerator and stir for 10 seconds.

[0058] Example 4

[0059] A thermal insulation material for hard rock tunnels in cold regions, the raw materials of which include: 90kg of PO 42.5 grade ordinary Portland cement, 12kg of pretreated silica, 15kg of grade II fly ash, 12kg of thermal insulation aggregate, 115kg of machine-made sand, 0.6kg of potassium silicate, 2.4kg of polycarboxylate water reducer, 0.2kg of polyether modified organic silicon defoamer, 1.7kg of accelerator, and 19kg of water.

[0060] The pretreated silica was prepared by the following specific operation: 4 kg of nylon 66 was added to 35 kg of 77% formic acid solution, stirred at 65°C for 100 min, 7 kg of ethyl orthosilicate was added and stirred for 18 min, 1.3 kg of nano-graphene oxide was added and stirred for 100 min, the temperature was lowered to -95°C, kept warm for 100 min, and freeze-dried.

[0061] The thermal insulation aggregate is composed of hydrophobic vitrified microspheres and expanded perlite in a mass ratio of 10:1.5. The hydrophobic vitrified microspheres are prepared by the following specific operations: 25 kg of hollow vitrified microspheres are added to 70 kg of sulfuric acid solution with a mass fraction of 77%, stirred at a temperature of 42 ° C for 18 minutes, filtered, washed, dried, added to 70 kg of ammonia solution with a mass fraction of 18%, stirred at a temperature of 42 ° C for 25 minutes, filtered, washed, dried, added to 70 kg of ethanol aqueous solution with a mass fraction of 45%, 1.3 kg of tridecafluorooctyl triethoxysilane is added thereto, hydrochloric acid is used to adjust the pH value of the system to 3-4, stirred at a temperature of 77 ° C for 80 minutes, the stirring speed is 3000r / min, filtered, and dried.

[0062] The quick-setting agent is prepared by the following specific operation: 1.5 kg of aluminum sulfate, 0.4 kg of citric acid, 1.3 kg of aluminum hydroxide, 1.8 kg of calcium formate, 1.3 kg of sodium methylenebisnaphthalene sulfonate, and 18 kg of water are mixed, stirred at a temperature of 75° C. for 100 min, 1.3 kg of diethanolamine is added, stirred for 100 min, and cooled to room temperature.

[0063] The above method for preparing the thermal insulation material suitable for hard rock tunnels in cold regions comprises the following steps:

[0064] S1. Add PO 42.5 grade ordinary Portland cement, pretreated silica, grade II fly ash, and thermal insulation aggregate into a mixer, and stir at a speed of 120 r / min for 90 s to obtain a premix;

[0065] S2. Add machine-made sand, potassium silicate and water to the premix and mix evenly. Then add polycarboxylic acid water reducer, polyether modified silicone defoamer and accelerator and stir for 10 seconds.

[0066] Example 5

[0067] A thermal insulation material for hard rock tunnels in cold regions, the raw materials of which include: 85 kg of PO 42.5 grade ordinary Portland cement, 12.5 kg of pretreated silica, 14.5 kg of grade II fly ash, 15 kg of thermal insulation aggregate, 110 kg of machine-made sand, 0.8 kg of potassium silicate, 2.3 kg of polycarboxylic acid water reducer, 0.3 kg of polyether modified organic silicon defoamer, 1.5 kg of accelerator, and 20 kg of water.

[0068] The pretreated silica was prepared by the following specific operation: 3 kg of nylon 66 was added to 40 kg of 75% formic acid solution, stirred at 70°C for 90 min, 8 kg of ethyl orthosilicate was added and stirred for 15 min, 1.5 kg of nano-graphene oxide was added and stirred for 90 min, the temperature was lowered to -90°C, kept warm for 90 min, and freeze-dried.

[0069] The thermal insulation aggregate is composed of hydrophobic vitrified microspheres and expanded perlite in a mass ratio of 10:2. The hydrophobic vitrified microspheres are prepared by the following specific operations: 20 kg of hollow vitrified microspheres are added to 80 kg of 75% sulfuric acid solution, stirred at 45°C for 15 minutes, filtered, washed, dried, added to 80 kg of 15% ammonia solution, stirred at 45°C for 20 minutes, filtered, washed, dried, added to 80 kg of 40% ethanol aqueous solution, 1.5 kg of perfluorooctanesulfonylaminopropyl triethoxysilane is added thereto, hydrochloric acid is used to adjust the pH value of the system to 3-4, stirred at 75°C for 90 minutes at a stirring speed of 2500 r / min, filtered, and dried.

[0070] The accelerator is prepared by the following specific operation: 2 kg of aluminum sulfate, 0.3 kg of citric acid, 1.5 kg of aluminum hydroxide, 1.5 kg of calcium formate, 1.5 kg of sodium methylenebisnaphthalene sulfonate, and 15 kg of water are mixed, stirred at a temperature of 80° C. for 90 min, 1.5 kg of triisopropanolamine is added, stirred for 90 min, and cooled to room temperature.

[0071] The above method for preparing the thermal insulation material suitable for hard rock tunnels in cold regions comprises the following steps:

[0072] S1. Add PO 42.5 grade ordinary Portland cement, pretreated silica, grade II fly ash, and thermal insulation aggregate into a mixer, and stir at a speed of 150 r / min for 90 s to obtain a premix;

[0073] S2. Add machine-made sand, potassium silicate and water to the premix and mix evenly. Then add polycarboxylic acid water reducer, polyether modified silicone defoamer and accelerator and stir for 10 seconds.

[0074] Comparative Example 1

[0075] Ordinary shotcrete insulation material

[0076] A thermal insulation material for hard rock tunnels in cold regions, the raw materials of which include: 85kg of PO 42.5 grade ordinary Portland cement, 12.5kg of silicon dioxide (i.e. silica fume, purchased from Shijiazhuang Baijiang Mineral Products Co., Ltd., 1250 mesh), 14.5kg of Class II fly ash, 15kg of thermal insulation aggregate, 110kg of machine-made sand, 0.8kg of potassium silicate, 2.3kg of polycarboxylic acid water reducer, 0.3kg of polyether modified silicone defoamer, 1.5kg of alkali-free liquid accelerator (purchased from Jiangsu A Lai Te New Materials Co., Ltd., model SL15), and 20kg of water.

[0077] The thermal insulation aggregate is composed of vitrified microspheres and expanded perlite in a mass ratio of 10:2.

[0078] The above method for preparing the thermal insulation material suitable for hard rock tunnels in cold regions comprises the following steps:

[0079] S1. Add PO 42.5 grade ordinary Portland cement, silicon dioxide, grade II fly ash, and thermal insulation aggregate into a mixer, and stir at a speed of 150 r / min for 90 s to obtain a premix;

[0080] S2. Add machine-made sand, potassium silicate and water to the premix and mix evenly. Then add polycarboxylic acid water reducer, polyether modified silicone defoamer and accelerator and stir for 10 seconds.

[0081] Comparative Example 2

[0082] A thermal insulation material for hard rock tunnels in cold regions, the raw materials of which include: 85 kg of PO 42.5 grade ordinary Portland cement, 6.99 kg of pretreated silica, 14.5 kg of grade II fly ash, 5.51 kg of nylon 66, 15 kg of thermal insulation aggregate, 110 kg of machine-made sand, 0.8 kg of potassium silicate, 2.3 kg of polycarboxylate water reducer, 0.3 kg of polyether modified organic silicon defoamer, 1.5 kg of accelerator and 20 kg of water.

[0083] The pretreated silica was prepared by the following specific operation: 8 kg of ethyl orthosilicate was added to 40 kg of 75% formic acid solution and stirred for 15 min, 1.5 kg of nano graphene oxide was added and stirred for 90 min, the temperature was lowered to -90°C, kept warm for 90 min, and freeze-dried.

[0084] The thermal insulation aggregate is composed of hydrophobic vitrified microspheres and expanded perlite in a mass ratio of 10:2. The hydrophobic vitrified microspheres are prepared by the following specific operations: 20 kg of hollow vitrified microspheres are added to 80 kg of 75% sulfuric acid solution, stirred at 45°C for 15 minutes, filtered, washed, dried, added to 80 kg of 15% ammonia solution, stirred at 45°C for 20 minutes, filtered, washed, dried, added to 80 kg of 40% ethanol aqueous solution, 1.5 kg of perfluorooctanesulfonylaminopropyl triethoxysilane is added thereto, hydrochloric acid is used to adjust the pH value of the system to 3-4, stirred at 75°C for 90 minutes at a stirring speed of 2500 r / min, filtered, and dried.

[0085] The accelerator is prepared by the following specific operation: 2 kg of aluminum sulfate, 0.3 kg of citric acid, 1.5 kg of aluminum hydroxide, 1.5 kg of calcium formate, 1.5 kg of sodium methylenebisnaphthalene sulfonate, and 15 kg of water are mixed, stirred at a temperature of 80° C. for 90 min, 1.5 kg of triisopropanolamine is added, stirred for 90 min, and cooled to room temperature.

[0086] The above method for preparing the thermal insulation material suitable for hard rock tunnels in cold regions comprises the following steps:

[0087] S1. Add PO 42.5 grade ordinary Portland cement, pretreated silica, grade II fly ash, thermal insulation aggregate and nylon 66 into a mixer, and stir at a speed of 150 r / min for 90 seconds to obtain a premix;

[0088] S2. Add machine-made sand, potassium silicate and water to the premix and mix evenly. Then add polycarboxylic acid water reducer, polyether modified silicone defoamer and accelerator and stir for 10 seconds.

[0089] The fluidity of the thermal insulation material for cold-region hard rock tunnels obtained in Example 5 and Comparative Examples 1-2 was measured using a cement mortar fluidity tester with reference to GB / T 2419-2005 "Method for Determining Fluidity of Cement Mortar". The fluidity of the thermal insulation material for cold-region hard rock tunnels obtained in Example 5 was 230 mm, the fluidity of the thermal insulation material for cold-region hard rock tunnels obtained in Comparative Example 1 was 205 mm, and the fluidity of the thermal insulation material for cold-region hard rock tunnels obtained in Comparative Example 2 was 220 mm. All three were greater than 200 mm, and were suitable for use as shotcrete.

[0090] The initial setting time and final setting time of the thermal insulation material for hard rock tunnels in cold regions obtained in Example 5 and Comparative Examples 1-2 were tested with reference to the corresponding testing methods in JC477-2005 "Accelerators for Shotcrete".

[0091] like Figure 1 As shown, the initial setting time and final setting time of the thermal insulation material for hard rock tunnels in cold regions obtained in Example 5 are both the shortest, which is better than that of Comparative Examples 1-2 (P < 0.05).

[0092] With reference to GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)", the insulation materials for cold-region hard rock tunnels obtained in Example 5 and Comparative Examples 1-2 were cast into 40 mm × 40 mm × 160 mm specimens, and then standardly cured for 28 days. The compressive strength tests were performed on the specimens of each group cured for 1 day and 28 days.

[0093] like Figure 2 As shown, the 1d compressive strength and 28d compressive strength of the thermal insulation material for hard rock tunnels in cold regions obtained in Example 5 are both the highest, which are better than those of Comparative Examples 1-2 (P < 0.05), and the 1d compressive strength of the thermal insulation material for hard rock tunnels in cold regions obtained in Example 5 can reach more than 80% of the 28d compressive strength, which proves that the early strength of the thermal insulation material for hard rock tunnels in cold regions obtained in Example 5 is high.

[0094] With reference to ISO 22007-2:2015, the thermal conductivity of concrete specimens in the above groups after 28 days of standard curing was measured using the transient flat plate heat source method.

[0095] According to T / CECS 864-2021 "Ultra-High Performance Concrete Test Method Standard", the early-age autogenous shrinkage of the above-mentioned groups of standard cured concrete specimens was measured.

[0096] like Figure 3 As shown, the thermal conductivity of the thermal insulation material for hard rock tunnels in cold regions obtained in Example 5 is the lowest, and its thermal insulation effect is the best, which is better than that of comparative examples 1-2 (P < 0.05); the early-age autogenous shrinkage of the thermal insulation material for hard rock tunnels in cold regions obtained in Example 5 is the smallest, which proves that it can reduce the risk of cracking.

[0097] The permeability grade of the concrete samples of the above groups after 28 days of standard curing was tested with reference to GB 50164-2011 "Concrete Quality Control Standard". The permeability grade of the concrete obtained in Example 5 exceeded P20, the permeability grade of the concrete obtained in Comparative Example 1 was P15, and the permeability grade of the concrete obtained in Comparative Example 2 was P17.

[0098] After the above-mentioned standard curing for 28 days, the concrete specimens of each group were immersed in 20±2℃ water for 4 days, and the immersion water level was 25.0±5.0mm higher than the top surface of the specimen. After the immersion, the specimens were taken out and the moisture on the surface of the specimens was wiped off, and the appearance dimensions were measured and weighed. Each specimen was placed in a specimen box and then placed in a freeze-thaw box, with a 20mm gap between the specimen and the wall of the specimen box. In the quick freezing test, clean water should be injected into the specimen box, and the height of the water level should be 50mm higher than the specimen. When the temperature in the freeze-thaw box drops to -18℃, the timing starts, and the freezing time in each freeze-thaw cycle is 4h. After the freezing is completed, water with a temperature of 19.0±1.0℃ is immediately added, and the water adding time is within 10min. The water level is more than 20mm higher than the specimen, and the melting time is 4h. After the melting is completed, the freeze-thaw cycle is considered to be over, and the next freeze-thaw cycle can be carried out.

[0099] The freeze-thaw test was stopped after 100 freeze-thaw cycles, the compressive strength of the specimens was tested, and the strength loss rate was calculated.

[0100] Strength loss rate = 1-compressive strength of the sample after 100 freeze-thaw cycles ÷ original compressive strength of the sample × 100%

[0101] like Figure 3 As shown, the thermal insulation material for cold-region hard rock tunnels obtained in Example 5 has the lowest strength loss rate and the best anti-freeze-thaw effect, which is better than that of Comparative Examples 1-2 (P < 0.05).

[0102] The applicant believes that this is because the present invention dissolves nylon 66 (PA66) in a formic acid solution, deposits and combines nano-silicon dioxide particles on the PA66 skeleton, and then cooperates with the sheet structure of nano-graphene oxide to form an aerogel structure through freeze drying. The aerogel structure not only has a large number of pore structures inside, but also can effectively extend the heat transfer route and greatly reduce the thermal conductivity. At the same time, it is compounded with cement, has good dispersibility in the slurry, effectively increases the viscous resistance of floating in the slurry, and significantly improves the homogeneity of the mixture. The present invention further combines the hollow vitrified microspheres with a fluorine-containing silane coupling agent after acid and alkali treatment, which not only has excellent hydrophobic effect, but also is compounded with pre-treated silica and cement, which not only effectively reduces density and thermal conductivity, improves thermal insulation performance, but also makes the mortar light and high-strength, which can improve the workability of concrete mixtures, reduce rebound, and increase the thickness of one injection. Since the pretreated silica obtained by the present invention has a strong water retention and slow-release ability, it plays a role of water slow-release internal curing inside the concrete in the cold eastern zone, which not only significantly reduces freeze-thaw damage, reduces the risk of cracking, ensures later strength development, and improves durability, but also can compensate for shrinkage, reduce cracking, and extend the service life of the tunnel.

[0103] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A thermal insulation material for hard rock tunnels in cold regions, characterized in that: The raw materials include, by mass: 70-100 parts of cement, 10-14 parts of pretreated silicon dioxide, 10-16 parts of fly ash, 10-20 parts of thermal insulation aggregate, 100-120 parts of machine-made sand, 0.5-1.2 parts of potassium silicate, 2-2.6 parts of water reducer, 0.1-0.5 parts of defoamer, 1-2 parts of accelerating setting agent, and 17-22 parts of water; The pretreated silica was prepared by the following specific operation: adding nylon 66 to formic acid solution, stirring at 60-80°C for 1-2h, adding ethyl orthosilicate and continuing to stir for 10-20min, adding nano graphene oxide and stirring for 1-2h, cooling to -100 to -80°C, keeping warm for 1-2h, and freeze-drying; The thermal insulation aggregate comprises: hydrophobic vitrified microspheres and expanded perlite, and the mass ratio of the hydrophobic vitrified microspheres to the expanded perlite is 10:1-3.

2. The thermal insulation material for hard rock tunnels in cold regions according to claim 1, characterized in that: The mass ratio of nylon 66, tetraethyl orthosilicate and nano-graphene oxide is 1-5:5-10:1-2.

3. The thermal insulation material for hard rock tunnels in cold regions according to claim 1, characterized in that: The mass fraction of the formic acid solution is 70-80%.

4. The thermal insulation material for hard rock tunnels in cold regions according to claim 1, characterized in that: The hydrophobic glass microspheres are prepared by the following specific operation: adding the hollow glass microspheres to a sulfuric acid solution, stirring at 40-50°C for 10-20 minutes, filtering, washing, drying, adding to an ammonia solution, stirring at 40-50°C for 10-30 minutes, filtering, washing, drying, adding to an ethanol aqueous solution, adding a fluorinated silane coupling agent thereto, adjusting the pH value of the system to 3-4, stirring at 70-80°C for 1-2 hours, filtering, and drying.

5. The thermal insulation material for cold region hard rock tunnel according to claim 4, characterized in that: The mass ratio of the hollow glass microspheres to the fluorine-containing silane coupling agent is 10-30:1-2.

6. The thermal insulation material for hard rock tunnels in cold regions according to claim 4, characterized in that: The fluorine-containing silane coupling agent is tridecafluorooctyl triethoxysilane or perfluorooctanesulfonylaminopropyl triethoxysilane.

7. The thermal insulation material for hard rock tunnels in cold regions according to claim 1, characterized in that: The accelerator is prepared by the following specific operation: aluminum sulfate, citric acid, aluminum hydroxide, early strength agent, dispersant and water are mixed, stirred at 70-90° C. for 1-2 hours, organic alcohol amine is added, stirred for 1-2 hours, and cooled to room temperature.

8. The thermal insulation material for cold region hard rock tunnels according to claim 7, characterized in that: The mass ratio of aluminum sulfate, citric acid, aluminum hydroxide, early strength agent, dispersant, water and organic alcohol amine is 1-3:0.1-0.5:1-2:1-2:1-2:10-20:1-2; The organic alcohol amine is at least one of ethanolamine, diethanolamine and triisopropanolamine; The early strength agent is calcium formate and / or sodium nitrate; The dispersant is sodium methylene bisnaphthalene sulfonate.

9. A method for preparing a thermal insulation material for a hard rock tunnel in a cold region according to any one of claims 1 to 8, characterized in that: The steps include: S1. Stir cement, pretreated silica, fly ash and thermal insulation aggregate for 50-100 seconds to obtain a premix; S2. Add machine-made sand, potassium silicate and water to the premix and mix evenly. Then add water reducer, defoamer and accelerator and stir for 5-15s.

10. A method for applying the thermal insulation material for hard rock tunnels in cold regions according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: pre-wetting the surface to be sprayed, and then spraying the thermal insulation material for hard rock tunnels in cold regions as claimed in any one of claims 1 to 8 onto the surface, with a spraying thickness of 30 to 50 mm.

Citation Information

Patent Citations

  • Preparation method of composite material based on nylon 66 aerogel

    CN111269567A

  • Self-heat-preservation anti-freezing lining structure for traffic tunnel in seasonally frozen soil area

    CN112983468A

  • Nylon composite material and preparation method thereof

    CN115710120A

  • Antifreezing and high-ductility composite, and preparation method and use thereof

    GB2613670A

  • Composition for repairing and reinforcing concrete structure comprising high strength mortar, and method of repairing and reinforcing concrete structures using the same

    KR101941179B1